THE EFFECT OF EXPIRED BREAD MEAL AS CORN SUBSTITUTION IN DIET ON BROILER PERFORMANCE - Kismiati, S.; Sarengat, W.; Atmomarsono, U.; Salaamun, R.; Alvi, M.F. (Diponegoro University, 2010)
An experiment was conducted to investigate the expired bread meal used as corn substitution in thebroiler diets to optimally the product performance. One hundred day old chick (DOC) male broilerswere given the same diet until 2 weeks old, and then given the treatment diet until 7 weeks of age. ACompletely Randomized Design was used in this study. Data were analyzed by variance of analysis, andfollowed by Duncan’s Multiple Range Test The treatments were : T0 = control feed (without expiredbread meal), T1 = corn substituted with 10% expired bread meal, T2 = corn substituted with 20%expired bread meal, T3 = corn substituted with 30% expired bread meal and T4 = corn substituted with40% expired bread meal. The result indicated that corn substituted with expired bread meal up to 40%has not significantly affected on carcass weight, carcass percentage and feed conversion, but decreasedsignificantly on feed consumption and body weight gain. It can be concluded that the use of expiredbread meal 30% of the proportion of corn produced the most optimal broiler performance. Thesubstitution corn with expired bread meal 40% was decreased body weight gain.